2015
DOI: 10.1016/j.molliq.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of sodium bis(2-ethylhexyl) sulfosuccinate in aqueous solutions: Modulation of micelle structure and interactions by cyclodextrins investigated by small-angle neutron scattering

Abstract: Keywords:Sodium dioctyl sulfosuccinate DOSS Aerosol-OT AOT Surfactant Micelle Cyclodextrin Small-angle neutron scattering SANS FormulationThe modulating effects of α-cyclodextrin (α-CD) and hydroxypropyl β-cyclodextrin (HP-β-CD) on micelles formed in water by the double tail surfactant sodium bis(2-ethylhexyl) sulfosuccinate (also known as dioctyl sulfosuccinate (DOSS) or Aerosol-OT (AOT)) have been investigated using small angle neutron scattering (SANS). SANS data were fitted to the core-shell oblate ellipso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
1
6
1
Order By: Relevance
“…This result demonstrates that self-assembly simulations permit us to explore this polydispersity in a way that simulations beginning with preassembled structures cannot. The aggregation numbers observed in Figure A are close to the aggregation numbers reported from experiments in the low concentration limit, around the critical micellar concentration. , …”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…This result demonstrates that self-assembly simulations permit us to explore this polydispersity in a way that simulations beginning with preassembled structures cannot. The aggregation numbers observed in Figure A are close to the aggregation numbers reported from experiments in the low concentration limit, around the critical micellar concentration. , …”
Section: Resultssupporting
confidence: 83%
“…The aggregation numbers observed in Figure 4A are close to the aggregation numbers reported from experiments in the low concentration limit, around the critical micellar concentration. 24,85 The micelles observed in the isotropic phase are on average smaller than those observed experimentally. The time-averaged mean aggregation number in the simulations of 1 wt % at 293 K about 12 (Table S1), which deviates from the experimentally observed value of about 31.…”
Section: ■ Computational Detailsmentioning
confidence: 70%
See 1 more Smart Citation
“…The ethyl moiety on the EAN cation leads to the formation of polar and nonpolar segregated domains, which increases the solubility of hydrocarbons and, as a result, can increase the CMC of PEO-PPO-PEO block copolymers [ 37 ]. Surface tension measurements [ 38 ] of the ionic low-molecular weight surfactant Aerosol-OT (AOT) in EAN indicated a spontaneous, endothermic and entropy-driven micellization process similar to that observed in water [ 39 ]. The surface activity of AOT in EAN is weaker than that in water due to the relatively higher dielectric constant and viscosity of EAN [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless, these claims clearly contradict the accepted behaviour of the system, yet the aggregation behaviour at concentrations below 29 wt % Na-AOT has been cited as if accurate as recently as 2015. 93 A further possible complication is the report from Hubbard et al that Na-AOT samples of some concentrations can take over three months to fully equilibrate. 94,95 This raises the question of whether or not different research groups have reported upon the system at different states of equilibration, rather than the truly energetically preferred state.…”
Section: Sodium Aot: Lamellar Phase Literature Reviewmentioning
confidence: 99%